Equivalent linkage representation of a railway wheelset for dynamic simulation with kinematic non-linearities. Issue 1 (2nd January 2023) - Vishnu, S.; Singh, S. P.; Saha, S. K.
Abstract : In this work, a four-link serial-chain mechanism which is an equivalent representation of railway wheelset is proposed. Through this representation, it has been shown that the concepts like instantaneous roll centre, dynamically varying link lengths, and shape constraints can be used to account for wheel–rail contact into the existing multibody formulation. An outline of the framework is described for dynamic analysis of a suspended wheelset model. It is possible to conveniently include kinematic non-linearities into the equations of motion. Usually, these terms are overlooked while using elastic approach for wheel–rail contact. Essentially, benefits of two conventionally followed approaches, namely, elastic, and constrained contact, are exploited in this work. Through a parametric study, it was found that such nonlinear terms have significant impact on hunting stability of wheelsets having high conicity.